PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN LINGKUNGAN - Hilmi Hilmi; Mutia Rinanda (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aims to examine the effect of profitability and leverage on environmental disclosure of companies on the Indonesia Stock Exchange. This study uses secondary data in the form of annual reports during 2016-2018 accessed on www.idx.co.id. The population in this study is 641 companies and the samples are 48 companies selected using the Purposive sampling method. The data analysis method used is multiple linear regression with the help of the SPSS program. The results show that profitability affect environmental disclosure and leverage affect negative environmental disclosure.